Teachers' dispositional mindfulness and the quality of their relationships with children in Head Start classrooms. (December 2017) - Becker, Brandon D.; Gallagher, Kathleen C.; Whitaker, Robert C.
Abstract: The quality of teachers' relationships with children is a key predictor of children's later social emotional competence and academic achievement. Interventions to increase mindfulness among teachers have focused primarily on the impacts on teachers' subjective well-being, but not on the quality of their relationships with children. Furthermore, none of these interventions have involved preschool teachers. To consider the potential of mindfulness-based interventions to improve the quality of teachers' relationships with preschool-aged children, we examined data from an online survey of 1001 classroom teachers in 37 Pennsylvania Head Start Programs. Using path analysis we investigated the association between teachers' dispositional mindfulness and the quality of their relationships with children (conflict and closeness). We further examined whether this association was mediated by teacher depressive symptoms and moderated by perceived workplace stress. Higher levels of dispositional mindfulness among teachers were associated with higher quality relationships with children (less conflict and greater closeness). The association between greater dispositional mindfulness and less conflict was partially mediated by lower depressive symptoms, and the conditional direct effect of mindfulness on conflict was stronger when perceived workplace stress was lower. These findings suggest that preschool teachers who have higher levels of dispositional mindfulness may experience higher quality relationships with children in their classrooms. Interventions to increase levels of dispositional mindfulness among early childhood educators may improve their well-being along with the quality of their relationships with children, potentially impacting children's educational outcomes. The potential impacts of such interventions may be even stronger if structural and systemic changes are also made to reduce workplace stress.